ChatGeppetto - an AI-powered Storyteller - Lima, Edirlei Soares De; Feijó, Bruno; Cassanova, Marco A.; Furtado, Antonio L. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2023: Anais do XXII Simpósio Brasileiro de Jogos e Entretenimento Digital, 2023)
In this paper we introduce a novel highly interactive process to generate natural language narratives on the basis of our ongoing work on semiotic relations. To the two basic components of interactive systems, namely, a software tool and a user interface, we add a third component – AI agents, understood as an upgraded rendition of software agents. Our semiotic relations approach considers four ways of composing new narratives from existing narratives. Along what semioticians call the horizontal syntagmatic axis, one can form the new narrative by combining two or more previous narratives. Along the vertical paradigmatic axis, the new narrative may emerge as a similar version, which imitates the previous one, possibly in a different context. Along the depth meronymic axis, the hierarchic narrative levels, such as plot, event, and scene, are explored, allowing either expansion or summarization. Lastly, the antithetic consideration, rather than adding a dimension, aims at some form of reversal, through the adoption of opposite values. A fully operational prototype is described. Its name, ChatGeppetto, conflates the skilled Geppetto, who fashioned Pinocchio, an early case of artisanship-produced human level intelligence, with ChatGPT, which operates as the main AI agent component. To run the experiments, we concentrated on book narratives.